Business Process Modeling in Systems of Systems - Santos, Jean Marcos; Graciano Neto, Valdemar Vicente; Nakagawa, Elisa Yumi (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2020: Anais do II Workshop em Modelagem e Simulação de Sistemas Intensivos em Software, 2020)
The Systems of Systems area has received more attention due to the growing demand from society and organizations for more integrated and complex services. As a result, the challenge for engineers to model business processes in increasingly complex systems has also grown. The main contribution of this paper is to provide a wide overview about the business process modeling approaches in the context of systems of systems. Through a systematic mapping of the literature, 33 studies were selected to answer four research questions. The analysis of the extracted data showed that the approaches to business process modeling did not evolve in the necessary way. This result shows that the area needs to receive more attention from researchers.